Geophysical, geochemical and geodetical signals of reawakening at Turrialba volcano (Costa Rica) after almost 150 years of quiescence - Martini, F. (2010)
Turrialba is a basaltic–andesitic stratovolcano (3340 masl), in the Cordillera Volcánica Central in Costa Rica. After the last eruption (1864–1866), volcanic manifestations were limited to weak fumarolic discharge (continuous since 1980) from the summit. From 1996 onward, the degassing activity has progressively been increasing, reaching its climax after 2005. New fumaroles have appeared in the Central and West summit craters, the latter now being the most active, and in the fracture system in between, showing sulphur deposits and progressively increasing degassing rate. In 2004, fumaroles and new fissures have appeared on the SW outer and SSW distal flanks, the latter being located along a major NE-oriented tectonic lineament. Fumarolic temperatures at the bottom of the West crater have increased from 88 to 282 °C in early 2008. Changes in chemical and isotopic compositions of discharged fluids have shown a progressive enhancing of the magmatic signature since 2001. Since late 2007, SO2 flux, measured with mini-DOAS, has increased two orders of magnitude (1 t/day in 2002 to 740 t/day in January 2008). The enhanced gas discharge at Turrialba volcano has caused significant interference on tropospheric O3 measurements at 2–3 km altitude ~50 kmWfrom the volcano. Seismic swarms followed an increasing trend consistent with that of the fumaroles. The maximum seismic activity to date, up to thousands of events/day, was recorded in mid 2007. An inflationary trend was observed in the crater area. In this paper we present for the first time all the available data on the activity of Turrialba volcano. New geophysical, geodetical and geochemical data and published geophysical and geochemical data are presented and discussed as a whole. The multidisciplinary approach indicated that from 1996 to 2009 three stages, deriving by the delicate equilibrium between the hydrothermal and the magmatic reservoirs, were recognized. The magmatic-dominated phase is still prevailing as evidenced by the fact that, while completing the present paper, on the 4th of January 2010 at 16.57 (GMT) a loud explosion occurred at the West crater and was followed by three others spaced out every 10 min. These events were interpreted as associated with phreatic eruptions.